Nevoid basal-cell carcinoma syndrome (Gorlin Syndrome): report of two cases and review of the literature - Castro-Mujica, María del Cármen (2017)
Gorlin syndrome (GS) is a genetic disorder with an autosomal dominant inheritance pattern, with complete penetrance and variable expressivity. GS is caused by germline mutations in the genes PTCH1 or SUFU, which are components of the Sonic hedgehog molecular pathway. GS is characterized by the presence of multiple nevoid basal cell carcinomas, odontogenic cysts, calcification of the brain sickle, and lesions in the palms and soles. This study is the first to report cases in Peru of patients with GS who underwent genetic evaluation and counseling. We present two GS cases that meet the clinical criteria for the syndrome and review the literature.